Beyond Writing Assistance: Exploring Students’ Critical Dependence and Autonomous Learning in Chatgpt-Supported Writing Classes - Ranti Destia Widyanti; Destri Wahyuningsih (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Writing is an important skill in English language learning, and the development of Artificial Intelligence (AI), especially ChatGPT, has provided new support for students in writing classes. However, there are still different views regarding its benefits and challenges in learning. Therefore, this study aimed to explore students’ perceptions of the use of ChatGPT in writing classes at STKIP Insan Madani Airmolek, with a particular focus on the tension between AI dependency and learner autonomy — an underexplored dimension in the Indonesian EFL context. This study used a qualitative descriptive design involving 14 students selected through purposive sampling. The data were collected through open-ended questionnaires and semi-structured interviews, then analysed using the Miles and Huberman model. The findings showed that students generally had positive perceptions of ChatGPT because it helped improve grammar, vocabulary, idea development, and writing efficiency. However, several challenges were found, such as irrelevant responses and concerns about dependency on AI, as well as ethical considerations regarding academic integrity and responsible AI use. In conclusion, ChatGPT can be a useful supporting tool in writing classes if it is used wisely under lecturers’ guidance to maintain students’ critical thinking and independent learning.